Reflectometric System for Continuous and Automated Monitoring of Irrigation in Agriculture - Egidio De Benedetto; Giuseppe Cannazza; Antonio Masciullo; Christian Demitri; Andrea Cataldo (Advances in Agriculture)
In this work, a time domain reflectometry (TDR)-based system for continuous and diffused monitoring of soil water content in agriculture is presented. The proposed TDR-based system employs elongate sensing elements (SEs). In practical application, each wire-like SE is buried along the cultivation row to be monitored, and through a single TDR measurement it is possible to retrieve the water content profile of the cultivation along the length of the SE. By connecting the TDR-based monitoring system to the irrigation machines, it would be possible to automatically start/stop irrigation based on the actual water requirement of the cultivations, thus favoring precision agriculture and enhancing irrigation efficiency. To demonstrate the feasibility of the proposed monitoring solution, a dedicated hardware+software platform was developed and the TDR-based system was experimented in open-field cultivations.